Etapas e volume de treinamento das ginastas Brasileiras participantes de Jogos Olímpicos (1980-2004) - Schiavon, L. M. [UNESP]; Paes, R. R.; Moreira, A.; Maia, G. B M (Desafio Singular, Lda, 2011)
Results from Brazilian female Artistic Gymnastics improved over the past 10 years at an international level of competition. This study aimed at describing career development process in sports through a qualitative research resorting to the Oral History method. Ten Brazilian gymnast players in Olympic Games from 1980 to 2004 participated in the study. The information they provided allowed for the identification of specific variables present in their long term preparation: structure and organization of their practice, duration of the preliminary preparation phases, volume of daily practice in different phases of training, and length of time for the achievement of better results. © FTCD/CIDESD.
Training phases and volume of training for Brazilian female gymnasts in Olympic Games (1980-2004)
Keywords: Gymnastics; Olympic Games; Sports training